Prevalence of MTD among Patients with Functional Dysphagia. Issue 3 (August 2018) - Hamdan, Abdul-Latif; Ziade, Georges; Khalifee, Elie; Al Souky, Nader; Jaffal, Hussein; El Natout, Tamer
Objective: To assess the prevalence of laryngeal muscle tension patterns among patients with functional dysphagia. Study Design: Retrospective study. Setting: The study took place at a university medical center. Material and Methods: The medical charts and laryngeal video recordings were reviewed for all patients who presented with dysphagia and who were referred for barium swallow between 2012 and 2017. A total of 170 cases were identified. Only those with normal findings on barium swallow and the absence of vocal fold pathology (exudative lesions, masses or tumors, paresis, and paralysis), referred to as functional dysphagia, were included in this study. Information retrieved included swallowing and phonatory symptoms in addition to patterns of laryngeal muscle tension. Results: The mean ± SD age of the total group was 41.90 ± 15.10 years with a male:female ratio of 4:1. Seventy-five percent had evidence of at least 1 type of laryngeal muscle tension pattern. The most common pattern was type III, characterized by supraglottic anteroposterior compression (13 of 20), followed by type II, characterized by medial compression of the false vocal folds (5 of 20); only 1 patient had muscle tension pattern type IV, characterized as sphincter-like closure of supraglottic structures. The most common laryngopharyngeal symptom was throat discomfort when swallowing (35%), followed by throat clearing and choking/coughing when eating and drinking (25%). Conclusion: The high prevalence of laryngeal muscle tension pattern among patients with functional dysphagia supports the notion that laryngeal tension may be one of the underlying causes of dysphagia.